2017
DOI: 10.1016/j.eurpsy.2017.01.224
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Psychotherapeutic Interventions for Management of Post-stroke Depression: A Bayesian Network Meta-analysis of 27 Randomized Controlled Trials

Abstract: Introduction: Poststroke depression (PSD) constitutes an important complication of stroke, leading to great disability as well as increased mortality. Since which treatment for PSD should be preferred are still matters of controversy, we are aiming to compare and rank these pharmacological and nonpharmacological interventions.Methods and analysis: We will employ a network meta-analysis to incorporate both direct and indirect evidence from relevant trials. We will search PubMed, the Cochrane Library Central Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…This systematic review is reported according to PRISMA statement extension for NMA (Appendix 1) 36 and conducted according to a priori-established protocol registered with PROSPERO (CRD42016049049) 37 .…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review is reported according to PRISMA statement extension for NMA (Appendix 1) 36 and conducted according to a priori-established protocol registered with PROSPERO (CRD42016049049) 37 .…”
Section: Methodsmentioning
confidence: 99%